Implications of digital twin applications on management accounting practices to support competitive advantage: A foresight view from the Saudi business environment - Abdelhalim, Abeer M. (International Journal of Innovative Research and Scientific Studies, 2025)
The study addresses the transformative implications of digitalization, notably the integration of digital twins, in various manufacturing and management application areas, including accounting information systems, operational costs, and organizational changes. It emphasizes the need for comprehensive policies and training programs to enhance preparedness and adaptability within Saudi organizations while highlighting the importance of robust cybersecurity measures and strategic partnerships with technology providers. This study applied exploratory research and a qualitative case study to collect data using multiple tools such as interviews, observations, and content analysis. The findings emphasize the proactive and forward-thinking approach required for organizations to effectively navigate the digital landscape, embrace emerging technologies, and maintain flexibility to drive growth and success. The study's primary objective is to enhance the comprehension of how digital twins can generate additional value and provide a competitive edge within the Saudi business landscape. This emphasizes the significance of utilizing digital technologies to maintain a leading position in the global market. The research enhances our understanding of how Digital Twins can bolster management analytics (MA) practices to gain a competitive advantage, yet it underscores a significant gap for future studies. Current investigations have largely centered on individual technologies, such as big data, AI, or IoT, concerning MA, rather than exploring the intricate interactions among multiple technologies within Digital Twins. A more in-depth examination of these integrations across different applications is essential to identify the challenges and impacts on MA practices, especially considering the reliance on extensive unstructured data. However, the findings are somewhat limited as they are derived from a case study of a leading energy company, which may not accurately represent broader circumstances due to diminished uncertainty and competitive pressures. Future research should investigate these associations across varied contexts to deepen our understanding.